STRENGTHENING THE DIGITAL-BASED WASTE BANK AND MULTI-PARTY COOPERATIVE MODEL TO IMPROVE SUSTAINABLE WASTE MANAGEMENT IN JATINANGOR DISTRICT, SUMEDANG - Subagyo, Ahmad; Winata, Widia; Ahmad, Gofur; Istikomah, Istikomah; Hekmatyar, Gulbudin; Lintang, Lintang; Rifal, Rifal (LPPM Univ. Ibn Khaldun Bogor, 2025)
The issue of waste management in Jatinangor, Sumedang, has increased rapidly following the trends of urbanization and consumption, while conventional management capacity has become increasingly limited. This PKM program aims to strengthen community literacy, adopt a digital-based waste bank, and encourage the formation of multi-party cooperatives to manage waste in an accountable and sustainable manner. The methods used include socialization, practical training, digital application implementation, mentoring, and impact evaluation with a participatory community approach. The training results showed an increase in understanding, the formation of waste bank management groups, and the development of a digital financial recording system, which has the potential to be replicated in other villages. In conclusion, community synergy, technological innovation, and multi-stakeholder cooperatives are effective in building a modern and inclusive waste management system, as well as supporting the circular economy and the achievement of SDGs.